The Impact of The Covid-19 Pandemic on The Finances of Local Government Units - The Case of Poland - Katarzyna OWSIAK (Communications of International Proceedings, 2021)
The experience of many crises leads to the thesis that in democratic systems in which the public authorities include self-government authorities, the duties and responsibility for the consequences of the crisis fall in a significant part, if not primarily, on self-government authorities, because it is at the self-government level (local) the effects of crises are felt the most. Hence, actions and measures taken by central authorities, in conditions of high uncertainty, may facilitate or hinder local authorities in mitigating the effects of crises. The latest experiences related to the COVID-19 pandemic provide an excellent field for verification of the above thesis. During the pandemic crisis, the governments of many countries around the world made various, sometimes chaotic and controversial decisions to apply various institutional solutions limiting the effectiveness of local authorities. An example may be the controversy between federal authorities, state or local authorities (e.g. New York) in the USA, also in Great Britain. Hence, the subject of this study is to present the impact of the institutional, legal and financial solutions applied by the Polish government during the pandemic in 2020 on the possibilities of combating the effects of the crisis. The quantitative analysis confirmed that while the increase in the income of local government units in Poland may prove a good financial condition as an aggregate, it does not exclude the need for further research and, above all, taking into account the significant diversified financial situation of individual local government units.
Keywords: COVID-19 Pandemic; Financial Law; Fiscal Rules; Local Government; Local Government Finances